Newly defined acute exacerbation of idiopathic pulmonary fibrosis with surgically-proven usual interstitial pneumonia: risk factors and outcome - Okuda, Ryo; Hagiwara, Eri; Katano, Takuma; Ikeda, Satoshi; Sekine, Akimasa; Kitamura, Hideya; Baba, Tomohisa; Okudela, Koji; Ohashi, Kenichi; Ogura, Takashi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: In 2016, the diagnostic criteria for the acute exacerbation (AE) of idiopathic pulmonary fibrosis (IPF) were revised. However, there have been published few clinical reports on AE–IPF published using the new criteria. The aim of this study was to investigate the incidence of, risk factors for, and mortality due to newly defined AE. Moreover, differences between triggered AE and idiopathic AE were investigated. Methods: The retrospective study was conducted including all IPF patients diagnosed with surgically-proven usual interstitial pneumonia through multi-disciplinary discussion between January 2006 and December 2015. Data were retrieved from a clinical chart review. Results: A total of 107 patients with newly diagnosed 107 IPF patients were included. The cumulative incidence of initial AE were 9.6% at 1 year, 16.8% at 2 years, 23.9% at 3 years, and 37.3% at 4 years after diagnosis. Three risk factors for AE–IPF development were identified: 1) the minimum peripheral ozygen saturation level of ≤88% during the 6-minute walk test at the time of diagnosis; 2) forced vital capacity (FVC) decreasing by ≥10% in 1 year; and 3) diffusion capacity of the lungs for carbon monoxide (DLco) decreasing by ≥15% in 1 year. There were no significant differences in background (excluding C-reactive protein), survival and treatment between patients with triggered AE and those with idiopathic AE. Conclusions: The 6-minute walk test and an annual decline in FVC and DLco were predictive factors for AE incidence. The causes of AE–IPF did not affect the prognosis or treatment options in clinical practice.